The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1117/12.887623
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of cooperative autonomous underwater vehicles for Antarctic exploration

Abstract: The present work describes the development of two collaborative Autonomous Underwater Vehicles (AUV) for Antarctic exploration to use them in the Ecuadorian Expeditions to the Scientific Base Pedro Vicente Maldonado in Antarctica. One vehicle is an AUV, called TAUV, with classical torpedo architecture, can work as a platform to transport scientific payload in a determined path in open waters. The TAUV length is 2m and diameter of 0.16m and has got three degree of freedom: pitch, yaw and surge. The vehicle achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Although AUV platforms have been used to map under the sea ice in limited studies [1,6] this research demonstrated the ability to conduct concise transects covering 12.42 hectares at very high spatial resolution (5 cm) and high degrees of precision (0.01 m drift) of this cryptic marine environment. Aside from mapping sea ice thickness we have uniquely resolved smooth ice from platelet ice at 5 cm resolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although AUV platforms have been used to map under the sea ice in limited studies [1,6] this research demonstrated the ability to conduct concise transects covering 12.42 hectares at very high spatial resolution (5 cm) and high degrees of precision (0.01 m drift) of this cryptic marine environment. Aside from mapping sea ice thickness we have uniquely resolved smooth ice from platelet ice at 5 cm resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Autonomous underwater vehicles (AUVs) have been used in the Arctic since the 1970s, and increasingly in the Antarctic in recent years, to acoustically survey the geometric properties of the underside surface of sea ice [1][2][3][4][5]. There are various motivations that have initiated this research, including mapping sea ice thickness [6]; describing the roughness characteristics of the ice to determine wind and water drag coefficients for dynamical modeling [7]; and monitoring the transition of multiyear sea ice to first year sea ice [8].…”
Section: Introductionmentioning
confidence: 99%